Komunikasi Organisasi Dewan Ambalan Gugus Depan SMA Negeri Kerjo Karanganyar Dalam Proses Pembentukan Mental Dan Karakter - Suyadi; Hindra H, Nurnawati; Muadz, Muadz (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
The importance of communication for humans cannot be separated, as well as for an organization, with good communication an organization can run smoothly and successfully, and vice versa, lack of communication can cause chaos and problems arise in an organization. Based on initial observations, the organization of the Front Group Standing Board of Kerjo Karanganyar State High School in the process of mental and character formation was considered lacking, one of which was a lack of responsibility and good manners. The formulation of the problem in this research is how the communication of the Front Gugus Ambalan Council Organization of Kerjo Karanganyar State High School is carried out in the process of mental and character formation. The aim of this research is to describe and analyze the organizational communication of the Kerjo State High School Standing Board in the process of mental and character formation. This research uses a qualitative description. The subjects of this research were Scoutmasters, Ambalan Council administrators and Ambalan Pradewan. The types and sources of data used are primary data and secondary data. The technique for determining informants is purposive sampling technique. Data collection techniques use library research and triangulation techniques. The data analysis technique uses the Miles and Huberman interactive model, namely data reduction and drawing conclusions. The results of the research show that the organizational communication of the Kerjo Karanganyar State High School Ambalan Council Organization, both upward and downward communication, has been going well, but there are several inhibiting factors that have an impact on the mental and character formation process of Pradewan Ambalan, namely differences in status, lack of self-confidence, awareness and miscommunication. Keywords: Organizational Communication, mentality and character, Standing Board